Determination of Rice Field Potential Index Based on Geographic Information System in Gowa Regency - Rahmatya, Desi; Achmad, Mahmud; Samsuar (Salaga Journal, 2024)
The Index of Land Potential (IPL) is a land evaluation method that aims to identify and utilize land according to its potential. Through IPL, it is expected to achieve optimal productivity and land sustainability. This research aims to determine the Paddy Field Potential Index with the IPL weighting method using Geographic Information Systems (GIS) in Gowa Regency. In this research, the method used is a tiered quantitative approach, where each parameter is given an appropriate weight. Overlapping techniques were applied to various maps used to assess land potential, including aspects of slope, soil type, lithology, hydrology, and disaster risk. The results of this study include a land potential index map and a map of paddy field potential in Gowa Regency. In the LMI, the dominating classes are low and very low, covering an area of 156,885.34 ha (72%), while the use of paddy fields in the very high and high potential classes covers an area of 20,604.48 ha (39%). The relationship between productivity and IPL is explained through the equation IPL = 0.1025P + 4.9539 with a value of R2 = 0.7809, which indicates that an increase in IPL can be a guide to increasing the productivity of rice plants..